Dwujęzyczne nazewnictwo na liniach kolejowych na Zaolziu w Republice Czeskiej - Petr Drapa (Studia Slavica)
The paper deals with bilingual nomenclature on railway lines in Zaolzie region. This paper deals with the process of introducing bilingual (Czech-Polish) signs on the railway in Zaolzie region. It conducts a survey of the current situation of the Polish national minority and the approach of Polish organizations, mainly the Congress of Poles in the Czech Republic (Kongres Polaków w Republice Czeskiej), to bilingualism. The work deals with the theoretical aspects of bilingualism in the Czech Republic, for example the conditions under which bilingual signs are introduced. However, the most important is the practical part, which describes the introduction of bilingualism at railway stations. The work also deals with other areas where Polish is used - e.g. timetables, train announcements at stations… It also tries to draw attention to the problems with the introduction of bilingualism, which persist to this day.